Understanding The Perception Of Imams On Drug Addiction In Kuala Lumpur - Imran Bin Abd Rahman
The problem of drug abuse is an issue that will never end. Although various efforts have been made, this issue remains an issue that has no solution. The fact is this problem requires the cooperation of all parties so that all levels of society are aware that drug abuse will damage themselves and their families. This study aims to mobilize the role of the Imam through the institution of the mosque to help those who are stuck with the problem of drug addiction in the mosque community. However, in order to achieve that goal, this study was first conducted to identify how Imams perceive drug addiction. The study was conducted among Imams who work in mosques around Kuala Lumpur, where the mosques are currently under observation by the National Anti-Drug Agency. This study was conducted through qualitative methods and semi-structured interview forms. Interview forms are created, which include three open and closed questions. There were seven respondents consisting of who are Imams of mosques in Kuala Lumpur. The results of the findings of this study show that the Imam's perception of drug addiction is self-destructive, bad behaviour, broken family, and not being able to be self-sufficient or helpless, which lives expecting the help of others. In terms of attitude, this finding found that being helpful because of their responsibilities as Imams, religious decree based on fellow believers, which is highly demanded, humanity and understanding due to friends who are involved with drug abuse problems. Meanwhile, in terms of experience, the findings of this study show that many complaints from wives whose husbands are involved in drug abuse have aggressive actions and menace community peace, especially in mosques. The findings of these three elements show that mosque Imams need to be given knowledge and guidance, and skills for them to help these drug addicts properly and help restore these groups.